Exploring the neuroprotective potential of naringin following spinal cord injury in rats: improving sensory and motor function through combating inflammation and oxidative stress - Moradi, Fatemeh; Fakhri, Sajad; Kiani, Amir; Abbaszadeh, Fatemeh; Farzaei, Mohammad Hosein; Echeverría, Javier (Frontiers in Pharmacology, 2025)
IntroductionSpinal cord injury (SCI) leads to widespread cascades of inflammatory and oxidative factors. This pathological condition damages nerves and causes neurological disorders. To address these complex conditions, it is important to identify therapeutic candidates that affect multiple dysregulated signaling mediators and targets. Some phytochemicals such as naringin (NAI) with neuroprotective, antioxidant, and anti-inflammatory effects can be seen as a possible candidate for treating neurodegenerative diseases.PurposeTherefore, this study aims to evaluate the impact and mechanism of NAI on sensory and motor function in rats with SCI.Materials and methodsIn total, 35 rats were studied in five groups, including sham, SCI, and three groups treated with intrathecal administration of NAI (5, 10, and 15 mM). After the injury, sensorimotor behavioral tests and weight changes were performed for 4 weeks. On the 28th day, the serum of rats was checked to measure biochemical factors such as catalase, glutathione, and nitrite and the activity of metalloproteinases 2 (MMP-2) and MMP-9. Also, histological changes in spinal cord tissue were evaluated weekly for 4 weeks.Results and discussionNAI treatment demonstrated significant benefits in rats with SCI, including reducing pain, improvement in motor performance, and attenuated animal weight gain. Besides, NAI decreased the lesion area of spinal tissue and enhanced neuronal survival at both ventral and dorsal horns of spinal tissue. Furthermore, serum analysis revealed that NAI increased MMP-2 activity and catalase and glutathione levels while decreasing nitrite and MMP-9 activity.ConclusionThe intrathecal administration of NAI can be proposed as a proper alternative in the treatment of sensory-motor disorders caused by SCI through neuroprotective, anti-inflammatory, and antioxidant mechanisms.